Introduction to the special issue of Human Technology: Games and play at the margins: Between visibilities and invisibilities - Chee, Florence M. (Human Technology, 2019)
How does one code for silence? In which ways, subtle and otherwise, are voices present and accounted for, yet not in certain spaces? Sometimes, the important work is indeed being done, but the means of communicating that contribution faces substantial barriers to its conveyance. This is the everyday reality of scholarship, and one goal of this special issue of Human Technology has been to focus on the publication of research that provides insight into the niches and nuances of online game communities. Academic researchers and media scholars stand to be bridges, rather than barriers, in this process. Among members of the media, their multitudinous audiences, stakeholders in a game industry in convulsions, and decision-makers at every level of education and training has been frustration at the lack of progress, and sometimes regression, when it comes to opportunities to create and participate.